2017
DOI: 10.3389/fendo.2017.00038
|View full text |Cite
|
Sign up to set email alerts
|

Expression Patterns and Correlations with Metabolic Markers of Zinc Transporters ZIP14 and ZNT1 in Obesity and Polycystic Ovary Syndrome

Abstract: Polycystic ovary syndrome (PCOS) is associated with infertility, increased androgen levels, and insulin resistance. In adipose tissue, zinc facilitates insulin signaling. Circulating zinc levels are altered in obesity, diabetes, and PCOS; and zinc supplementation can ameliorate metabolic disturbances in PCOS. In adipose tissue, expression of zinc influx transporter ZIP14 varies with body mass index (BMI), clinical markers of metabolic syndrome, and peroxisome proliferator-activated receptor gamma (PPARG). In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 67 publications
0
9
0
Order By: Relevance
“…Previous studies reported that zinc contents in the skin, muscle, and bone is reduced in obese mice [ 49 ], and serum zinc concentration is significantly lower in obese children than that in matched normal-weight children [ 50 – 52 ]. Meanwhile, the expressions of some zinc transporters, such as ZNT1 and ZNT6 in brain [ 53 ], ZIP14 in adipose [ 54 , 55 ], and ZnT4, ZnT5, ZnT9, ZIP1, ZIP4 and ZIP6 in leukocyte [ 56 ], were inversely correlated with obesity. Herein, our study provided similar evidence that ZIP12 expression in testis significantly decreased in obese mice, which is associated with reduced sperm zinc content, high sperm ROS level, poor sperm quality and male subfertility.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies reported that zinc contents in the skin, muscle, and bone is reduced in obese mice [ 49 ], and serum zinc concentration is significantly lower in obese children than that in matched normal-weight children [ 50 – 52 ]. Meanwhile, the expressions of some zinc transporters, such as ZNT1 and ZNT6 in brain [ 53 ], ZIP14 in adipose [ 54 , 55 ], and ZnT4, ZnT5, ZnT9, ZIP1, ZIP4 and ZIP6 in leukocyte [ 56 ], were inversely correlated with obesity. Herein, our study provided similar evidence that ZIP12 expression in testis significantly decreased in obese mice, which is associated with reduced sperm zinc content, high sperm ROS level, poor sperm quality and male subfertility.…”
Section: Discussionmentioning
confidence: 99%
“…The subjects in the study were 80 women, aged 15–45 years, from the South Khorasan province of Birjand. The sample size was estimated to be 19.3 persons based on the formula for comparing 2 means, and the results of the Maxwell study and the homeostasis model assessment (HOMA) index with S1=0.6, S2=1.8, d=1.4, α=0.05 and β=0.1, in which 20 women in each group were considered [17].…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies reported that zinc contents in the skin, muscle, and bone were reduced in obese mice [49], and serum zinc concentration was signi cantly lower in obese children than that in matched normal-weight children [50][51][52]. Meanwhile, the expressions of some zinc transports, such as ZNT1 and ZNT6 in brain [53], ZIP14 in adipose [54,55], and ZnT4, ZnT5, ZnT9, ZIP1, ZIP4 and ZIP6 in leukocyte [56], were inversely correlated with obesity. Herein, our study provided similar evidence that ZIP12 expression in testis signi cantly decreased in obese mice, which was associated with reduced sperm zinc content, high sperm ROS level, poor sperm quality and male subfertility.…”
Section: Discussionmentioning
confidence: 99%